Lower impact forces but greater burden for the musculoskeletal system in running shoes with greater cushioning stiffness. Issue 2 (1st February 2023) - Malisoux, Laurent; Gette, Paul; Backes, Anne; Delattre, Nicolas; Theisen, Daniel
ABSTRACT: In a recent randomised trial investigating running shoe cushioning, injury risk was greater in recreational runners who trained in the shoe version with greater cushioning stiffness (Stiff) compared to those using the Soft version. However, vertical impact peak force (VIPF) was lower in the Stiff version. To investigate further the mechanisms involved in the protective effect of greater cushioning, the present study used an intra-subject design and analysed the differences in running kinematics and kinetics between the Stiff and Soft shoe versions on a subsample of 41 runners from the previous trial. Data were recorded in the two shoe conditions using an instrumented treadmill at 10 km.h −1 . VIPF was confirmed to be lower in the Stiff version compared to the Soft version (1.39 ± 0.25 vs. 1.50 ± 0.25 BW, respectively; p = 0.009, d = 0.42), but not difference was observed in vertical loading rate ( p = 0.255 and 0.897 for vertical average and instantaneous loading rate, respectively). Ankle eversion maximal velocity was not different ( p = 0.099), but the Stiff version induced greater ankle negative work (−0.55 ± 0.09 vs. −0.52 ± 0.10 J.kg −1 ; p = 0.009, d = 0.32), maximal ankle negative power (−7.21 ± 1.90 vs. −6.96 ± 1.92 W.kg −1 ; p = 0.037, d = 0.13) and maximal hip extension moment (1.25 ± 0.32 vs.1.18 ± 0.30 N.m.kg −1 ; p = 0.009, d = 0.22). Our results suggest that the Stiff shoe version is related to increased mechanical burden for the musculoskeletal system, especially around the ankle joint. Trial registration: ClinicalTrials.gov identifier: NCT03115437 .